Intraoperative Radiotherapy With INTRABEAM: Technical and Dosimetric Considerations - Sethi, Anil; Emami, Bahman; Small, William; Thomas, Tarita O. (Frontiers in Oncology, 2018)
Purpose We evaluate dose characteristics and clinical applications of treatment accessories used in intraoperative radiotherapy (IORT) and make site-specific recommendations for their optimal use. Methods and materials Dose measurements were performed for a low energy (50 kV) X-ray INTRABEAM source. For spherical, flat, surface, and needle applicators, the following dosimetric parameters were measured: depth-dose (DD) profiles, surface dose (Ds), output factors (OF), and target dose homogeneity (DH). Optical density versus exposure calibration films were employed to obtain 2-dimensional dose distributions in planes parallel and perpendicular to beam direction. Film results were verified via repeat dose measurements with a parallel-plate ionization chamber in a custom water tank. The impact of applicator design on dose distributions was evaluated. Results Spherical applicators are commonly used for treating the inner-surface of breast lumpectomy cavity. Flat and surface applicators provide uniform planar dose for head and neck, abdomen, and pelvis targets. Needle applicators are designed for kypho-IORT of spinal metastasis. Typically, larger applicators produce a more homogeneous target dose region with lower surface dose, but require longer treatment times. For 4-cm diameter spherical, flat, and surface applicators, dose rates (DR) at their respective prescription points were found to be: 0.8, 0.3, and 2.2 Gy/min, respectively. The DR for a needle applicator was 7.04 Gy/min at 5 mm distance from the applicator surface. Overall, film results were in excellent agreement with ion-chamber data. Conclusion IORT may be delivered with a variety of site-specific applicators. Appropriate applicator use is paramount for safe, effective, and efficient IORT delivery. Results of this study should help clinicians assure optimized target dose coverage and reduced normal tissue exposure.